Shoppers’ loyalty in online marketplace: The impact of interface quality, application incentives, and security/privacy through flow experience - Felicia Angela Adrianto; Oviliani Yenty Yuliana; Ferry Jaolis (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2023)
This study investigated the effects of Interface Quality, Application Incentives, and Security/Privacy on marketplace E-Loyalty through Flow experience. By prioritizing and improving these factors, marketplaces can foster a relational perspective that encourages users to develop a long-term relationship with the application, leading to sustained growth and success. Central to marketplace E-Loyalty is the relational perspective, which emphasizes consumers’ intention to establish a relationship with a marketplace application without shifting to competitors. Respondents were selected purposively to participate in an online survey, resulting in 305 usable responses. A partial least square-structural equation modeling (PLS-SEM) was employed to establish the measurement and structural fit of the data. The results confirmed that Interface Quality and Flow directly influenced E-Loyalty, while Interface Quality and Security/Privacy indirectly influenced Flow. Application Incentives were not found to bolster E-Loyalty directly and indirectly through Flow experience. This study provides a broader view of the importance of Interface Quality and Security/Privacy in promoting E-Loyalty with Flow while also offering a new perspective on the effect of Application Incentives on marketplace E-Loyalty from a relational standpoint.